LAKUAN TUTUR MENOLAK DALAM TRANSAKSI JUAL BELI: ANALISIS BENTUK DAN MAKNA TERHADAP PANGGALEH BABELOK PADA PASAR TRADISIONAL DI KABUPATEN SOLOK (The Refusal Utterances in Buying and Selling Transaction: The Analysis on Form and Meaning to Street Vendors on Traditional Markets in Solok Regency) - Imron Hadi (Balai Bahasa Sulawesi Selatan, 2015)
This study is aimed at describing the refusal utterances in buying and selling transaction by street vendors on traditional market in Solok Regency by using descriptive design. The utterances were recorded naturally when transaction between seller and buyer were happening. The recorded data were transcribed into written form in order to ease and determine the utterances of rejection. The analysis of data is focused on the refusal utterances that based Watt’s opinion. From the data analysis is found that there several kinds of rejection utterances by street vendors (1) be unconventionally indirect, (2) be pessimistic about ability to comply, 3) minimize the imposition, (4) give deference, 5) impersonalized the speaker and hearer, avoid the pronoun I and you, (6) state the FTA as an instance of general rule, and (7) go on record as incurring a debt, or as not indebting. The result of this study shows the seven types of rejection were dominated by unconventional indirect and followed by others. Some factors to use refusal utterances by street vendors are based on age, language, performance, and buying things by buyers.